Innovations in rural and agricultural finance: Bundling development services with agricultural finance: The experience of DrumNet - Campaigne, Jonathon; Rausch, Tom (International Food Policy Research Institute, 2010)
Agriculture is the largest economic sector in most African countries and remains the best opportunity for economic growth and poverty alleviation on the continent. Yet, sadly, the sector has been in decline over the past 40 years, and poor farmers have largely remained poor. This failure is due to many factors, including collapsed agricultural development banks, corruption, inadequate infrastructure, and poor soils and seeds. It has also occurred because smallholder farmers lack access to critical information, market facilitation, and financial intermediation services